Relación entre la calidad del agua del río Daule y la población de macroinvertebrados en los órdenes ephemeroptera, plecóptera y trichoptera, como bioindicadores, año 2018. - Tamayo Lema, Guadalupe Elizabeth (2018)
Human settlements have traditionally been carried out in regions close to rivers worldwide, since through them water is obtained for consumption of the various activities that man develops. These population settlements and their uncontrollable growth is one of the main causes of the pollution of the rivers, since waste is produced that is discharged to them. The Daule River located in the province of Guayas, Ecuador, is one of the main ones in the central zone of the region, however, previous studies indicate a serious deterioration in water quality due to the diverse impacts to which this is subject. basin mainly when it crosses the urban area of cities in transit. To achieve the proposed objectives, a comparison of the physical, chemical and biological parameters will be made, the presence of macroinvertebrates in the sampling stations will be determined and the incidence of water quality in the lower basin of the Daule River will be identified on the presence of macroinvertebrates. This work will be developed with the purpose of providing the professionals and corresponding organisms, a tool that can be used at the moment of projecting the possible solutions for the mitigation and control of the contamination of the Daule River in the study section. Keywords: Water, pollution, impact, waste.